1991
DOI: 10.1002/bmc.1130050205
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of gemfibrozil and its metabolites in plasma and urine by a fully automated high performance liquid chromatographic system

Abstract: Sensitive and specific methods for the simultaneous determination of gemfibrozil (Lopid), a lipid-lowering agent, and its metabolites in plasma and urine are described. The methods are based on a fully automated high performance liquid chromatographic (HPLC) system with fluorescence detection. Urine samples, diluted with acetonitrile, were directly analysed by HPLC using a flow and eluent programming method. In the case of plasma, gemfibrozil and its main metabolites were extracted from acidified samples and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…1), is a fibric acid derivative widely used as a lipid-regulating agent. Gemfibrozil undergoes extensive glucuronidation and oxidative metabolism (Nakagawa et al, 1991), with gemfibrozil 1-O-␤-glucuronide as one of the major metabolites in humans. Studies show that 32% of a gemfibrozil dose is excreted as a gemfibrozil conjugate in urine by 24 h after administration (Nakagawa et al, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1), is a fibric acid derivative widely used as a lipid-regulating agent. Gemfibrozil undergoes extensive glucuronidation and oxidative metabolism (Nakagawa et al, 1991), with gemfibrozil 1-O-␤-glucuronide as one of the major metabolites in humans. Studies show that 32% of a gemfibrozil dose is excreted as a gemfibrozil conjugate in urine by 24 h after administration (Nakagawa et al, 1991).…”
mentioning
confidence: 99%
“…Gemfibrozil undergoes extensive glucuronidation and oxidative metabolism (Nakagawa et al, 1991), with gemfibrozil 1-O-␤-glucuronide as one of the major metabolites in humans. Studies show that 32% of a gemfibrozil dose is excreted as a gemfibrozil conjugate in urine by 24 h after administration (Nakagawa et al, 1991). A recent report showed that the gemfibrozil glucuronide time-dependently inhibits CYP2C8 in vitro (Ogilvie et al, 2006).…”
mentioning
confidence: 99%
“…The mechanism of this action is not completely understood but may involve inhibition of peripheral lipolysis; reduced hepatic extraction of free fatty acids, which reduces hepatic triglyceride production; inhibition of synthesis and increased clearance of VLDL carrier, apolipoprotein B, which also reduces VLDL production and according to animal studies, reduced incorporation of longchain fatty acids into newly formed triglycerides, accelerated turnover and removal of cholesterol from the liver (stimulates incorporation of cholesterol precursors into precursors into liver sterols), and increased excretion of cholesterol in the feces [4][5][6][7][8][9] . Gemfibrozil is determined by high performance liquid chromatography (HPLC) [10][11][12][13] , liquid chromatography (LC) 14,15 , gas chromatography (GC) 16 19 , ion exchange 20 , hydrophobicity interaction 21 , and electrostatic interaction [22][23] . To our best knowledge, there are no reports for quantitative determination of gemfibrozil by using poly (gabapentin) film modified glassy carbon electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Gem is extensively metabolized and only about 5% of parent compound is retained. Its main metabolites include acyl glucuronide conjugates, accounting for 32% of all of Gem's metabolites in urine after administration [12][13][14]. For CA, 60% of the dose is conjugated as glucuronide metabolites in humans [15].…”
mentioning
confidence: 99%